SPATIAL DISTRIBUTION OF NEWBORNS WITH SICKLE CELL TRAIT IN SERGIPE, BRAZIL - Leite,Débora Cristina Fontes (2020)
ABSTRACT Objective: To use the spatial distribution of the sickle cell trait (SCT) to analyze the frequency of hemoglobin S (HbS) carriers in Sergipe. Methods: The sample consisted of all individuals born in Sergipe from October 2011 to October 2012 who underwent neonatal screening in the public health system. Tests were carried out in basic health units and forwarded to the University Hospital laboratory, where they were analyzed. We used spatial autocorrelation (Moran’s index) to assess the spatial distribution of heterozygous individuals with hemoglobinopathies. Results: Among 32,906 newborns, 1,202 showed other types of hemoglobin besides Hemoglobin A. We found a positive correlation between the percentage of black and multiracial people and the incidence of SCT. Most SCT cases occurred in the cities of Aracaju (n=273; 22.7%), Nossa Senhora do Socorro (n=102; 8.4%), São Cristóvão (n=58; 4.8%), Itabaiana (n=39; 4.2%), Lagarto (n=37; 4.01%), and Estância (n=46; 4.9%). Conclusions: The spatial distribution analysis identified regions in the state with a high frequency of HbS carriers. This information is important health care planning. This method can be applied to detect other places that need health units to guide and care for sickle cell disease patients and their families.